AGR626: Post Harvest Handling & Processing / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (2023)
State, discuss and relate knowledge on influence of crop physiology and maturity on produce's fresh post-harvest quality, primary processing, packaging and improving the preservation of fresh and semi-processed products.